2014
DOI: 10.1016/j.ajic.2014.03.026
|View full text |Cite
|
Sign up to set email alerts
|

Viral contamination of aerosol and surfaces through toilet use in health care and other settings

Abstract: The data collected in our study confirm that toilets are an important source of viral contamination, mainly in health care settings, where disinfection can have a crucial role in preventing virus spread.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 24 publications
2
87
0
Order By: Relevance
“…Enteric bacteria and viruses have been recovered from indoor air and environmental surfaces in areas sur-rounding toilets. 18,36,37 We reported that aerosolized simian rotavirus SA-11 38 survived best at midrange RH. 39,40 These results contradicted a prior study by Moe and Harper,41 in which the UK strain of calf rotavirus was reported to survive best at low and high RH, but not at high temperature.…”
Section: Virusesmentioning
confidence: 97%
“…Enteric bacteria and viruses have been recovered from indoor air and environmental surfaces in areas sur-rounding toilets. 18,36,37 We reported that aerosolized simian rotavirus SA-11 38 survived best at midrange RH. 39,40 These results contradicted a prior study by Moe and Harper,41 in which the UK strain of calf rotavirus was reported to survive best at low and high RH, but not at high temperature.…”
Section: Virusesmentioning
confidence: 97%
“…50,51 Air sampling for norovirus, to our knowledge, has not identified norovirus but was confined to settings without known norovirus infections. 72,73 The presence of norovirus on Copyright © 2015 American College of Occupational and Environmental Medicine. Unauthorized reproduction of this article is prohibited.…”
Section: Norovirusesmentioning
confidence: 99%
“…Nosocomial transmission of respiratory viruses occurs and is a consideration when implementing policies around cohorting of patients with CF. An Italian study tested hospital air and environmental surfaces of toilets for RV, and it was not detected, however, previous studies have identified influenza and respiratory syncytial virus in samples of hospital air and surfaces …”
Section: Introductionmentioning
confidence: 97%